2013
DOI: 10.2495/cmem-v1-n2-132-141
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of residence time distribution and local mean age of fluid to determine dead-zones in flow field

Abstract: Residence time and local mean age of fl uid are important parameters of the fl uid fl ow, with which we are able to detect the functioning and non-functioning zones. It is a novel approach to estimate the effect of dead-zones on chemical and biological processes. In this paper, we introduce a numerical tracer study, which is calibrated by fi eld measurements and which is applied in different cases such as settling tank and aeration tank of wastewater treatment. Using an advective-diffusive passive scalar trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Also, the use of fluorescent dyes as a tracer for colored wastewater (pulp and paper effluent) is not suitable. It was observed that the concentration of lithium chloride above 15% can hinder the microbial growth in the AT [34]. Hence, the toxicity of LiCl concentration on the growth of the microorganism population in the AT was examined by the Kirby Bauer method [35,36] and based on this study, the concentration of LiCl was kept below 15% for all the experiment, for all the RTD experiments.…”
Section: Rtd Experiments Of Tracermentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the use of fluorescent dyes as a tracer for colored wastewater (pulp and paper effluent) is not suitable. It was observed that the concentration of lithium chloride above 15% can hinder the microbial growth in the AT [34]. Hence, the toxicity of LiCl concentration on the growth of the microorganism population in the AT was examined by the Kirby Bauer method [35,36] and based on this study, the concentration of LiCl was kept below 15% for all the experiment, for all the RTD experiments.…”
Section: Rtd Experiments Of Tracermentioning
confidence: 99%
“…In the prior RTD studies performed on the AT, it was observed that it behaved like a typical mixing tank with backflow or exchange [3,40]. Conventional model as TIS and axial dispersion models were unable to satisfactorily portray the RTD curves [34,40,41]. Hence, the suggested compartment modelling was compared to conventional TIS model.…”
Section: Hydraulic Performance Of At and Aspmentioning
confidence: 99%
See 1 more Smart Citation
“…The light fractions of these liquids contain associated gases and low molecular weight hydrocarbons (e.g., CO 2 , H 2 S, N 2 , CI, C 2 , C 3 , n-C 4 , and i-C 4 ), while the rest of the oil contains a large amount of paraffinic hydrocarbons, naphthenic and aromatic compounds with molecular weight ranges from about 100 to 2000 g/mol. [4][5][6][7] During the decreasing of temperature, heavy hydrocarbon components in this range can crystallize and precipitate as a solid mass known as paraffin, which can be deposited on the walls of the pipe or processing equipment. This precipitation has both operational and economic implications for the oil industry.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of these phenomena and flake flow behavior in the dryer can be evaluated by determining the residence-time distribution (RTD), which is used to diagnose operational problems associated to the flow in continuous systems and to describe material displacement inside equipment by parameters such as external age, mean residence time, variance and standard deviation [13][14][15].…”
Section: Introductionmentioning
confidence: 99%